The Role of Metacognitive Skills in the Creativity of Design Course Students - Amir Masoud Jafari; Niloufar Malek; Saeid Khaghani (توسعه پایدار شهری)
Although architectural education has been searching for new educational models (student-centered, collaborative and analytical rather than informational and teacher oriented ones), it has not yet found its true educational model because of its design-oriented and proximity to architectural practice. The default of this research is that architectural education has a different nature than architectural practice. This means that merely designing and carrying out architectural projects is not a sufficient education, and it requires different processes and methods to achieve the right output into independent architectural designers. While the general perception is that the willingness and ability to respond to new problems and methods is largely internal and individual, new researches suggest that creativity is a skill that can be taught. Metacognition as the cognition of cognition, or simply, is a kind of reflective awareness of the upcoming action and a new topic in the area of creativity science. Metacognitive knowledge guides people to choose, evaluate, revise, or set aside cognitive tasks, goals and strategies according to their abilities and interests. Measuring and confirming this point leads to questioning common-sense understanding of the creative design process. There is an urgent need to get back to the issue of cognition and revise the knowledge about the creative design. After broad research in literature, using analytical comparison methods, this research has examined the effects of structural metacognitive skills on the development of creative thinking ability, for two groups of architectural students in the in two different semesters. The results show that the transfer of this ability in the design process affects the knowledge and surround of students on the subject of design, quality and its result.